Family Perception Towards Health Role in Filariasis Countermeasures Using the Health Belief Model Approach in Aceh Besar District - Elvin, Said Devi; Yusuf, Mutia; Hayati, Wirda; Alamsyah, Teuku (Kesmas, 2018)
Aceh Besar District is a filariasis endemic area. This endemic state is strongly influenced by people’s perception of filariasis countermeasures. This study aimed to determine relation between family perceptions towards health role in filariasis countermeasures using the Health Belief Model. An analytical survey was applied with a cross-sectional study approach. The study population was families at three villages that are Lambaro Bileu, Lambaet, and Cot Preh of Kuta Baro Primary Health Care. This represents 1,113 families with a sample of 92 families that were selected using a proportionate stratified random sampling technique. The study instrument was a questionnaire and data were analyzed in a univariate, bivariate, and multivariate. This study showed that the families’ perceived susceptibility to filariasis disease and the families’ perception of the benefits from filariasis preventive actions are influenced the health role in filariasis countermeasures (p value = 0.012 and 0.0001). However, the families’ perception of the seriousness of filariasis disease and the families’ perception of barriers in filariasis preventive action did not influence the health role in filariasis countermeasures (p value = 0.259 and 0.230). The families’ perceived benefits of preventive action were the dominant factor related to the families’ health role in filariasis countermeasures (OR = 12.863; 95% CI = 2.566–93.537) after adjusting with perceived susceptibility to diseases (OR = 8.316; 95% CI = 1.769–26.949).